Pengaruh Kualitas Produk Dan Harga Terhadap Keputusan Pembelian Produk Impor Cosrx Di Jakarta - Nurhafida; Joni Haryanto (JAMBIS : Jurnal Administrasi Bisnis, 2025)
Abstract.This study aims to determine the influence of product quality and price on purchasing decisions for importedCOSRX products in Jakarta. The method used was quantitative with an associative approach, and datacollection was conducted through a questionnaire administered to 160 respondents. Data analysis wasconducted using validity and reliability tests, classical assumptions, multiple linear regression, t-tests, Ftests, and coefficients of determination. The results indicate that product quality and price have a positiveand significant effect on purchasing decisions, both partially and simultaneously. Furthermore, price hasa more dominant influence than product quality. These findings are expected to provide strategic input forcompanies and contribute to the development of marketing science and consumer behavior.Keywords: Product Quality, Price, Purchasing Decisions, Imported Products, COSRX